Advances in Behavioral Economics and Finance Leadership Strategic Leadership, Wise Followership and Conscientious Usership in the Digital Century - Puaschunder, Julia (Contributions to Economics, 2022)
XI, 237 p. 18 illus., 17 illus. in color.